A fatal intractable ventricular fibrillation triggered by improper use of Xiaozhong Jiuwei Powder: integrated LC-MS chemical profiling unveils the cardiotoxic culprits - Abudu, Halidan; Yang, Zhaofei; Zhang, Lu; Sidike, Dilidaer; Guo, Liqiong; Fan, Haojun; Wubuli, Ayixiamuguli (Frontiers in Medicine, 2025)
IntroductionAcute poisoning from toxic substances significantly endangers human health, with poisoning-induced cardiac arrest representing a critical public health concern. Xiaozhong Jiuwei Powder (XZJWP), a traditional Chinese medicine (TCM) formulation used in Mongolian Medicine, is known for its antipyretic, analgesic, and anti-inflammatory properties. However, improper use of XZJWP can lead to severe adverse effects.MethodsIn this study, we report a fatal case of refractory ventricular fibrillation in a patient admitted to our hospital in autumn 2023, following the improper use of XZJWP. Despite intensive treatment, the patient succumbed to the condition 1 week later. To identify the toxic chemicals responsible for this outcome, a comprehensive chemical profiling of XZJWP was conducted using UPLC-Q-Orbitrap-HRMS.ResultsOur analysis identified 292 compounds, categorized into 24 major groups, with several toxic alkaloids detected. Notably, diester-diterpenoid alkaloids (DDAs), including aconitine, mesaconitine, and hypaconitine, were identified as key toxic compounds known to cause neurotoxicity and cardiotoxicity.DiscussionThese findings warrant caution in using XZJWP and other aconite-containing TCMs, emphasizing the need for public education on safe use and improved clinical management of related poisonings. The study provides crucial guidance for healthcare professionals in diagnosing and treating such toxicities.